Assessing the role of social media in shaping career aspirations among lecturers in Nigeria: A quantitative analysis - Adedotun, Kikelomo Oluwayemisi; Elegbede, Christie Bola; Lapite, Akolade Olubunmi; Idhalama, Ogagaoghene Uzezi; Aluede, Oyaziwo (Global Journal of Social Sciences Studies, 2024)
The study deployed a self-administered questionnaire via Google forms to generate data from a sample of 237 lecturers working in various tertiary institutions across Nigeria. The questionnaire was used to collect data on the use of social media by lecturers, their perceptions regarding the influence of such use on their career goals, and demographic data and other characteristics. First, descriptive statistics such as frequencies and percentages were used to summarize the data, supported by measures of central tendency. These analyses were done using the SPSS software. From the survey result, all the responded lecturers had ticked the "high extent" option, which means that social media affects their career aspirations to a great extent. Correspondingly, based on the response, it can be stated that all the respondents believe that social media platforms can be used for the purpose of career development as well as increasing recognition related to their professional outcomes. In addition, related to the responsibility of staying updated with the latest trends and best practices of the relevant business sectors as well as participating in online communities and discussions associated with their teaching disciplines in order to learn from others in the same field, responses were found to be highly unanimous. Correspondingly, based on the research questionnaire regarding the challenges faced by the Lecturers in Nigeria while using social media for career development purposes, there have been a number of common challenges that have come into view.